Analisis Analisis Kenaikan PPN 12% terhadap Praktik Penghindaran Pajak pada Pelaku UMKM: Studi Kasus Perilaku Kepatuhan di Indonesia - Wilda erinda Sutrisno; Puji Rahayu (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the impact of the increase in the Value Added Tax (VAT) rate to 12% under Law Number 7 of 2021 on Harmonization of Tax Regulations (UU HPP) on tax avoidance practices among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on the frequency, types of avoidance practices, and driving factors such as capital limitations, administrative complexity, and regulatory uncertainty. Using a mixed methods approach, this research combines questionnaire surveys of 1,000 MSMEs, in-depth interviews with 50 MSME owners, and secondary data analysis from reports by the Directorate General of Taxes (DJP) and the Central Statistics Agency (BPS). Quantitative analysis through multiple linear regression shows a positive coefficient of 0.42 for VAT increase (p-value <0.05), with R-squared of 0.68, while qualitative analysis identifies themes such as financial burden and avoidance strategies. Key findings indicate a decline in tax compliance from 70% to 55%, an increase in avoidance up to 25% (particularly fake invoices at 15% and underreporting income at 10%), and a Pearson correlation of 0.65 (p-value <0.01) between tax burden and avoidance frequency. These findings align with Tax Evasion Theory and Theory of Planned Behavior, highlighting risks of tax deficits up to 20% and social injustice for MSMEs. Recommendations include VAT rate reductions for small MSMEs, education campaigns, and strengthened friendly audits. Suggestions for further research include longitudinal studies and cross-country comparisons. This study provides innovative contributions through a hybrid model for measuring avoidance, despite limitations from self-reporting bias and limited generalization. Overall, these findings encourage more inclusive tax policy reforms to support MSME sustainability in Indonesia.